Energy and entropy : a dynamic duo - Leff, Harvey S., 1937- (Boca Raton : CRC Press, 2021)
Energy is typically regarded as understandable, despite its multiple forms of storage and transfer. Entropy, however, is an enigma, in part because of the common view that it represents disorder. That view is flawed and hides entropy's connection with energy. In fact, macroscopic matter stores internal energy, and that matter's entropy is determined by how the energy is stored. Energy and entropy are intimately linked. Energy and Entropy: A Dynamic Duo illuminates connections between energy and entropy for students, teachers, and researchers. Conceptual understanding is emphasised where possible through examples, analogies, figures, and key points. Features: Qualitative demonstration that entropy is linked to spatial and temporal energy spreading, with equilibrium corresponding to the most equitable distribution of energy, which corresponds to maximum entropy Analysis of energy and entropy of matter and photons, with examples ranging from rubber bands, cryogenic cooling, and incandescent lamps to Hawking radiation of black holes Unique coverage of numerical entropy, the 3rd law of thermodynamics, entropic force, dimensionless entropy, free energy, and fluctuations, from Maxwell's demon to Brownian ratchets, plus attempts to violate the second law of thermodynamics
4.5 PARAMAGNETS & FERROMAGNETS -- 4.5.1 Ideal paramagnet -- 4.5.2 Negative temperature -- 4.5.3 Ferromagnets -- 4.6 RUBBER BANDS -- 4.6.1 Rubber band experiment -- 4.6.2 Model of a rubber band -- 4.7 NUCLEAR BINDING ENERGY, FISSION, FUSION -- 4.8 JARZYNSKI FREE ENERGY EQUALITY -- 4.8.1 Examples of the Jarzynski equality -- Chapter 5: Radiation & Photons -- 5.1 EM RADIATION & TEMPERATURE -- 5.2 BLACKBODY RADIATION -- 5.3 THE PHOTON GAS -- 5.3.1 What is a photon gas? -- 5.3.2 Photon gas equations & graphs -- 5.3.3 Photon gas processes -- 5.4 KIRCHHOFF'S & PLANCK'S LAWS -- 5.4.1 Incandescent lamps
OCLC-licensed vendor bibliographic record.
Keywords: Thermodynamics; Entropy; Force and energy; SCIENCE / Energy; SCIENCE / General; SCIENCE / Gravity